Reingeniería de procesos en el área de producción para mejorar la productividad de la empresa de embutidos “la madrileña” sector Tiobamba, cantón Latacunga - Cajas Cayo, Ximena Alexandra (2015)
To develop the issue was raised as a general objective; Re-engineer the production process of the Company Sausages "La Madrileña" that allows to improve production processes in order to increase productivity, for which an analysis is made as to the structural, functional and organizational development processes derived meat carried out in the Production Department. The study was conducted with the support of documentary research, the theoretical foundation with contributions from several authors was structured; logical methods, field research and direct observation survey is used to determine the statistical results allow important findings to determine the vulnerabilities of the company for decision-making in reengineering….